Determinants of certified seeds accessibility among farming households in Imo State, Nigeria - Njoku Loveday Chukwudi; Ominikari Godwin O.; Umeh Ngozi Ekunyi; Nwabuisi Chibudo Joshua; Ebenehi Ojomugbokenyode; Musab Ibrahim; Ismail Ibrahim Hamma (Selekcija i Semenarstvo, 2025)
The study evaluated access to certified seeds among farming households in Imo State. One hundred and eighty respondents were selected for the study through a multistage sampling procedure. Data were collected on the availability, sources and access to certified rice seeds as well as the challenges of accessing certified rice seeds using a structured questionnaire and analysed with frequency counts, percentages and regression model. The results show that 57.4% of the respondents agreed that certified rice seeds were available to them and 79.4% sourced their seeds from local markets. Major challenges of accessing certified rice seeds indicated by the respondents include high cost of seeds (87.8%), lack of reliable certified seed (76.3%) and distance to source of purchase of certified seeds (44.4%). Most (62.6%) of the respondents have access to only one variety of certified rice seeds. The determinants of certified rice seeds access are respondents' age (r = 0.03; p < 0.05), household size (r = 0.04; p < 0.05), and contact with extension agents (r = 0.03; p < 0.05). The study concluded that farmers source their rice seeds from informal sources and did not have adequate access to certified seeds. Certified seeds companies should increase their sale point to facilitate farming households' access to reliable certified rice seeds at subsidized rates.